Atypical Antipsychotic Drug Unmasking Myasthenia Gravis in the Form of Myasthenia Crisis: A Case Report - Manoj Karki; Subodh Bashyal; Sudhan Devkota; Aprajita Sharma; Bidhata Rayamajhi; Niraj Kumar Jaiswal (Journal of Universal College of Medical Sciences, 2025)
Myasthenia gravis (MG) is the most common autoimmune disorder of the neuromuscular junction (NMJ). The clinical presentation of myasthenia gravis can range from mild ptosis to myasthenia crisis. A myasthenic crisis is characterized by respiratory failure secondary to respiratory or oropharyngeal muscle weakness requiring ventilatory support. Despite well healthcare access, 20% of patients still have myasthenia crisis as the first presentation of the disease. The diagnostic delay in myasthenia gravis can result in increase in the morbidity and mortality. We report the case of a 22-year-old female initially misdiagnosed with moderate depression for six months after the onset of symptoms and was treated with antipsychotics. Six months after this regimen precipitated the disease, she presented with acute respiratory failure and was diagnosed with a myasthenia crisis. Laboratory tests confirmed an elevated anti-AChR antibody level. The patient was treated with intravenous immunoglobulin (IVIG), corticosteroids, and anticholinesterase medication, resulting in significant recovery.